Preparation and Performance of Debian Mailing Lists Analysis - Buriánek, Jan; Bruckner, Tomáš, 1974-; Jelínek, Ivan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
This bachelor thesis is devoted to techniques and technologies within area of unstructured data processing. This processing includes building an infrastructure to make it feasible and obtaining data of all Debian mailing lists contents. In order to fullfil the main goal of this thesis, there has been downloaded entire content of Debian mailing lists. Debian mailing lists are a valuable source containing information about the Debian operating system and its software components. It proves that its software components are well-made reliable open-source tools. It is expected that this source of data is able to unveil plenty of unexpected relations. Used data and technologies as the Elasticsearch search and analysis engine are excelent tools and resources to conduct research over such type of comparism of mind and computer outputs as in case of Searle's axioms from article "Is Brain's mind a computer program?". This thesis is attempting to prove that such analysis is feasible.
Vedoucí práce: Tomáš Bruckner
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: informatika [obor bakal. práce]; bakalářské práce; bachelor's theses